Genetic Determinants of Host Range Specificity of the Wellington Strain of Xanthomonas axonopodis pv. citri - Rybak, Myrian Asucena (University of Florida, 2020)
Tesis para obtener el grado de Doctor (PhD), de la University of Florida, en 2005